Evidence for High Translational Potential of Mesenchymal Stromal Cell Therapy to Improve Recovery from Ischemic Stroke. Issue 9 (September 2013) - Eckert, Mark A; Vu, Quynh; Xie, Kate; Yu, Jingxia; Liao, Wenbin; Cramer, Steven C; Zhao, Weian
Although ischemic stroke is a major cause of morbidity and mortality, current therapies benefit only a small proportion of patients. Transplantation of mesenchymal stromal cells (MSC, also known as mesenchymal stem cells or multipotent stromal cells) has attracted attention as a regenerative therapy for numerous diseases, including stroke. Mesenchymal stromal cells may aid in reducing the long-term impact of stroke via multiple mechanisms that include induction of angiogenesis, promotion of neurogenesis, prevention of apoptosis, and immunomodulation. In this review, we discuss the clinical rationale of MSC for stroke therapy in the context of their emerging utility in other diseases, and their recent clinical approval for treatment of graft-versus-host disease. An analysis of preclinical studies examining the effects of MSC therapy after ischemic stroke indicates near-universal agreement that MSC have significant favorable effect on stroke recovery, across a range of doses and treatment time windows. These results are interpreted in the context of completed and ongoing human clinical trials, which provide support for MSC as a safe and potentially efficacious therapy for stroke recovery in humans. Finally, we consider principles of brain repair and manufacturing considerations that will be useful for effective translation of MSC from the bench to the bedside for stroke recovery.